(untitled) (TAMADDUN NURI JURNALI, 2024)
This article describes the ancient agricultural culture and its development in the Surkhandarya oasis and southern Uzbekistan. The early settled agricultural culture emerged during the Bronze Age, around the end of the 3rd millennium BCE, and is associated with the Sopolli culture. The Sopolli culture spread across a wide area, including parts of Tajikistan and the Dashly culture in northern Afghanistan. In the Neolithic period, the local populations were engaged in hunting and gathering, later transitioning to agriculture. During the Bronze Age, small micro-oases appeared in the Surkhandarya oasis, where irrigated agriculture developed. Archaeological findings, especially the grain storages discovered at the Sopollitepa and Jarkutan sites, indicate that ancient peoples cultivated wheat, barley, and grapes. Research shows that local communities used water supply and irrigation systems in their farming. Additionally, textile remnants found in Sopollitepa graves suggest that ancient farmers cultivated cotton and silk. The article discusses the development of agricultural culture from the Bronze Age to the early Iron Age.